Pharmacokinetics of Morphine and Morphine-6-Glucuronide During Postoperative Pain Therapy in Cardiac Surgery Patients - Ihmsen, Harald; Schüttler, Jürgen; Jeleazcov, Christian (European Journal of Drug Metabolism and Pharmacokinetics, 2021)
Background and Objective Morphine is a standard analgesic drug for postoperative pain therapy. This study aimed to evaluate the pharmacokinetics of morphine and its active metabolite morphine-6-glucuronide (M6G) in cardiac surgery patients during postoperative analgesia. Methods Twenty-five adult patients undergoing cardiac surgery received postoperative pain therapy by patient-controlled analgesia with intravenous bolus doses of morphine. Plasma concentrations of morphine and M6G were determined from arterial samples. Population pharmacokinetic parameters were estimated using nonlinear mixed-effects modeling. Results Data from twenty-one patients (aged 44-79 years) were analyzed. Pharmacokinetics were best described by a three-compartment model for morphine and a two-compartment model for M6G, linked by a transit compartment. Mean (+/- SD) population estimates for morphine were: clearance (CL) = 1.35 +/- 0.40 L/min, central volume of distribution (V-1) = 8.1 +/- 2.2 L, steady-state volume of distribution (V-ss) = 207 +/- 83 L, terminal elimination half-life (T-1/2(gamma)) = 177 +/- 50 min. Clearance of morphine was proportional to cardiac output. Mean (+/- SD) population estimates for M6G were: CL = 0.098 +/- 0.037 L/min, V-1 = 5.5 +/- 0.8 L, V-ss = 15.8 +/- 0.8 L, T-1/2(beta) = 227 +/- 74 min. The time to peak concentration of M6G after a bolus dose of morphine was 53 +/- 20 min. Clearance of M6G was proportional to estimated glomerular filtration rate. Conclusions The pharmacokinetics of morphine and M6G in pain therapy of cardiac surgery patients could be well described by standard compartmental models. Cardiac output was identified as a significant covariate for morphine clearance, whereas renal function was identified as the most significant covariate for clearance of M6G. These effects should be particularly considered if morphine is administered as a continuous infusion. The developed pharmacokinetic model also enables patient-controlled target-controlled infusion for pain therapy with morphine.
CRIS-Team WoS Importer:2021-02-26